The Hierarchy of'the Perfect Man According to Ibn 'Arabi - Diyab, Adib Nayif (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Hierarchy of'the Perfect Man According to Ibn 'Arabi